ECHO OF LODHRADI KASHAYA IN LIPID PROFILE OF TYPE 2 DIABETES MELLITUS PATIENTS - Singh, Varun Kumar; Reddy, Krc (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Lipid profile is matter to concern in fast changing lifestyle, and especially in diabetic mellitus (DM) patients. In arena of DM, obesity and high lipid contour is a causative problem and lead to generate the related problems too. Hence, tracking of lipid profile in DM patients is necessary as part of treatment approach. Hence, the present study was conducted to track the effect of Lodhradi Kashaya spray dried (LKSD) powder on lipid profile in Type 2 DM patients. Methods: Total 31 patients were taken following the guideline mention in Central Council for Research in Ayurveda and Siddha protocol for DM research. They were divided into two groups, Groups A and B and given LKSD (4 and 2 g TDS (three times a day), respectively, dissolved in water) for 3 months. They are investigated for their blood serum creatinine and lipid profile (cholesterol, low-density lipoprotein [LDL], high-density lipoprotein [HDL], very LDL [VLDL], and triglyceride). The patients response has also been noted regarding palatability acceptance and ease of administration. Â  Result: LKSD was found significantly effective in total cholesterol (p=0.001 and 0.073), triglyceride (p=0.002 and 0.003), HDL (pË‚0.001 and 0.026), LDL (p=0.563 and pË‚0.001), and VLDL (p=0.024 and 0.003). Patients had reported that formulation is easy to take in spite of its astringency in taste. Conclusion: Lodhradi Kashaya has capability to control and take care of disturbance in lipid profile in DM patients and thus enhance their living confidence. Â 